Effect of planting time on performance of Bermuda grass cv. Selection-I under Malwa plateau conditions of Madhya Pradesh - SETHIYA, RAJESH; KUMAR, ANUJ; DWIVEDI, S.K.; TRIPATHI, M.K. (Journal of Ornamental Horticulture, 2024)
Common Bermuda grass, Cynodon dactylon, is naturalized throughout the warmer regions of India. It is a tetraploid species with broad genetic variability. Bermuda grass has significant ecological, environmental and economic importance. Temperature is the main environmental factor that limits its adaptability to tropical and subtropical areas of the world. The impact of planting time on lawn grass fluctuates throughout the year. The present study was carried out to evaluate the effect of planting time on qualitative and quantitative parameters of Bermuda grass cv. Selection-1 at Experimental Farm, Department of Floriculture and Landscape Architecture, K.N.K. College of Horticulture, Mandsaur in the Malwa plateau region of Madhya Pradesh during 2022-23. The experimental material was consisting of 3 replications with 9 treatments of planting time i.e., T1 (September 20th), T2 (October 10th), T3 (October 30th), T4 (November 20th), T5 (December 10th), T6 (December 30th), T7 (January 20th), T8 (February 10th) and T9 (February 28th). The planting date, T9 (28th February) gives the best results with respect of most of the quantitative and qualitative parameters i.e. the highest survival percentage, number of stolons per plant, stolon internodal length, canopy height, fresh and dry clipping yield, maximum leaf chlorophyll content and turf quality.